Terahertz field effect in a two-dimensional semiconductor - Tomoki Hiraoka; Sandra Nestler; Wentao Zhang; Simon Rossel; Hassan A. Hafez; Savio Fabretti; Heike Schlörb; Andy Thomas; Dmitry Turchinovich (Nature Communications)
Abstract Layered two-dimensional (2D) materials offer many promising avenues for advancing modern electronics, thanks to their tunable optical, electronic, and magnetic properties. Applying a strong electric field perpendicular to the layers, typically at the MV/cm level, is a highly effective way to control these properties. However, conventional methods to induce such fields employ electric circuit - based gating techniques, which are restricted to microwave response rates and face challenges in achieving device-compatible ultrafast, sub-picosecond control. Here, we demonstrate an ultrafast field effect in atomically thin MoS2 embedded within a hybrid 3D-2D terahertz nanoantenna. This nanoantenna transforms an incoming terahertz electric field into a vertical ultrafast gating field in MoS2, simultaneously enhancing it to the MV/cm level. The terahertz field effect is observed as a coherent terahertz-induced Stark shift of exciton resonances in MoS2. Our results offer a promising strategy to tune and operate ultrafast optoelectronic devices based on 2D materials.